Stress, coping strategies and social support in patients with primary Sjögren's syndrome prior to disease onset: a retrospective case–control study. Issue 1 (14th February 2008) - Karaiskos, D; Mavragani, C P; Makaroni, S; Zinzaras, E; Voulgarelis, M; Rabavilas, A; Moutsopoulos, H M
Abstract : Objectives: Previous evidence suggests the role of psychological stress in triggering the onset of autoimmunity. We aimed to investigate whether stress following major and minor life events could precede the onset of primary Sjögren's syndrome (pSS). The role of coping strategies and social support, as compensating buffering mechanisms, was also explored. Methods: 47 patients with pSS were compared with two control groups: 35 patients with lymphoma (disease controls, DC) and 120 healthy controls (HC) with disease onset within the previous year. All subjects completed questionnaires assessing the occurrence of major and minor stressful events, coping strategies and social support prior to disease onset. Data analysis was performed by univariate and multivariate logistic regression models. Results: A higher number of patients with pSS reported the occurrence of negative stressful life events prior to disease onset compared with patients with lymphoma and HC, while the number and impact of daily hassles did not differ between the three groups. Coping strategies were defective and the overall social support was lower in patients with pSS compared with DC and HC groups. In the multivariate model, pSS status was associated with maladaptive coping and lower overall social support relative to DC and HC, as well as with an increased number of negative stressful life events compared with HC but not DC. Conclusions: Prior to disease onset, patients with pSS experience high psychological stress following major negative life events, without developing satisfactory adaptive coping strategies to confront their stressful life changes. Lack of social support may contribute to the relative risk of disease development.